A new generation of soil-geosynthetic interaction experimentation. Issue 4 (August 2019) - Morsy, A.M.; Zornberg, J.G.; Han, J.; Leshchinsky, D.
Abstract: A new device was developed to comprehensively assess the interaction between soil and reinforcement as well as the interaction between neighboring reinforcement layers in a reinforced soil mass, under both working and ultimate interface shear stress conditions. An understanding of these two interactions is required to assess the mechanical behavior of a geosynthetic-reinforced soil mass considering varying vertical reinforcement spacings. Specifically, the new device allows direct visualization of the kinematic response of soil particles adjacent to the geosynthetic reinforcement layers, which facilitates evaluation of the soil displacement field via digital image analysis. Evaluation of the soil displacement field allows quantification of the extent of the shear influence zone around a tensioned reinforcement layer. Ultimately, the device facilitates investigating the load transfer mechanisms that occur not only at the soil-reinforcement interface, but also at distances farther from the interface, thereby providing additional insight into the effect of vertical reinforcement spacing on a reinforced soil mass. Finally, the device allows monitoring of dilatancy within the reinforced soil mass upon shear stress generation at the interface between soil and reinforcement. Overall, the device was found to provide the measurements needed to adequately predict the strains developing both in reinforcement layers tensioned by direct application of external loads as well as in reinforcement layers tensioned by the shear transfer induced by adjacent geosynthetic reinforcements. Ultimately, the proposed experimentation technique allows generation of data required to evaluate the load transfer mechanisms amongst soil and reinforcement layers in reinforced soil structures. The strain magnitude in the neighboring reinforcements was found to exceed a magnitude of 10% of the strain magnitude obtained in the active reinforcement. The zone of shear stress transfer from the soil-reinforcement interface was found to exceed 0.2 m on each side of the active reinforcement.